2018
DOI: 10.1164/rccm.201801-0019le
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline and Repurposed Drugs for Fluoroquinolone-Resistant Multidrug-Resistant Tuberculosis: How Much Better Are They?

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…When national TB programs and partners used bedaquiline and delamanid alongside repurposed drugs such as linezolid in RR/MDR-TB treatment regimens according to WHO guidance, a high proportion of patients experienced sputum culture conversion by six months. endTB observational study findings are in-line with trials and smaller observational cohorts, which have generally reported six-month conversion outcomes ranging from 70% to 90% (10,11,13,19,37). This is notable because the endTB cohort included patient groups often excluded from trials (i.e., those with: HIV and low CD4; XDR-TB; previous treatment for MDR-TB; uncontrolled DM; coinfection with HIV and hepatitis B or C).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…When national TB programs and partners used bedaquiline and delamanid alongside repurposed drugs such as linezolid in RR/MDR-TB treatment regimens according to WHO guidance, a high proportion of patients experienced sputum culture conversion by six months. endTB observational study findings are in-line with trials and smaller observational cohorts, which have generally reported six-month conversion outcomes ranging from 70% to 90% (10,11,13,19,37). This is notable because the endTB cohort included patient groups often excluded from trials (i.e., those with: HIV and low CD4; XDR-TB; previous treatment for MDR-TB; uncontrolled DM; coinfection with HIV and hepatitis B or C).…”
Section: Discussionsupporting
confidence: 82%
“…(3)(4)(5)(6)(7) In 2012 and 2013, based on promising Phase II trial data, (8)(9)(10) stringent regulatory authorities approved the first new TB drugs in fifty years, bedaquiline (BDQ) and delamanid (DLM), offering hope for more effective and less toxic MDR-TB treatment. Since then, evidence generated from both randomized trials and observational studies has continued to support a role for these two drugs in MDR-TB treatment; (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) WHO has endorsed their use, gradually broadening the populations in which they might be used. ( TB).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that even in cases of FQ-R MDR TB including XDR TB, improved treatment outcomes can be achieved if appropriate drug combinations are used. Several recent studies using new drugs or repurposed drugs also yielded results consistent with the present study, in which the treatment success rate of XDR TB was not inferior to that of MDR TB [21, 23–25].…”
Section: Discussionsupporting
confidence: 91%
“…In a recent meta-analysis, the overall pooled successful treatment rate for FQ-S MDR TB was 62%–73% between 2009 and 2016, whereas that of FQ-R MDR TB including XDR TB was 51%–57% during the same period [3]. Recently, however, MDR/XDR TB treatment outcomes have been improved with the use of bedaquiline and delamanid [8, 20, 21], and repurposed drugs such as linezolid, clofazimine, and carbapenems also contributed to the improvement of MDR/XDR TB treatment outcomes [3, 7, 15, 22]. In the current study, FQ-R MDR TB was associated with more severe clinical symptoms such as cavitary lesions, bilateral disease, and higher acid-fast bacillus smear positivity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence, primarily from observational cohort studies, suggests that regimens that include new drugs such as bedaquiline (BDQ) and delamanid (DLM) or repurposed drugs such as linezolid and clofazimine can improve DR-TB outcomes, including culture conversion, treatment success and mortality 3032 . However, some observational cohort data have demonstrated high rates of reversion of culture conversion in patients with FQ-resistant TB, suggesting that longer durations (more than 6 months) of BDQ may be required for patients with more resistant disease 33 .…”
Section: Introductionmentioning
confidence: 99%